The diversity of megacities worldwide: Challenges for the future of mobility - Priester, R.; Kenworthy, Jeffery; Wulfhorst, G. (Spriger, 2013)
Megacities around the globe present bewildering combinations of transport patterns, transport infrastructure and other factors related to personal mobility. From the sprawling auto-dependent regions such as Los Angeles and Houston through the rail-based transit giants of Tokyo and Osaka, the informal-based public transport systems of Manila and Johannesburg, to the strong non-motorised sectors of Mumbai and the legendary traffic congestion of Bangkok, megacities are as diverse as they are many. But through this complexity and diversity, is it possible to find defining patterns? Can we simplify this perplexing picture? And through this process, is it possible to better understand and distinguish the array of mobility challenges that face such large cities? This chapter explores these questions through a cluster analysis of some 41 megacities across the globe, representing a vast range in wealth and other features. Exploiting The Millennium Cities Database for Sustainable Transport, which presents a very large, consistent and reliable set of transport and land use indicators for 100 cities worldwide, the study examines some 59 representative indicators covering land use and wealth characteristics, private, public and non-motorised mode mobility patterns, private and public transport infrastructure, transport investment patterns, transport energy use, transport externalities and other variables. The results suggest that megacities can be classified into six distinct types, which we have called Hybrid Cities, Transit Cities, Auto Cities, Non-Motorised Cities, Traffic-Saturated Cities and Paratransit Cities.The chapter provides a global mapping and description of these city-types, gives an overview on the variables used and the methodology for the cluster analysis and highlights the diversity of mobility patterns across these clusters by selected key variables. It explains how this advances our understanding of mobility in such cities. Finally, it presents the key mobility challenges that characterise each set of cities. The cluster results provided a framework for the selection of cities explored by scholars in the city mobility stories that form the major part of this book.